Ski deflection during the carving turn in para-alpine sit skiing - Nakashima, H.; Yoshioka, S.; Ishige, Y. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Ski deflection strongly influences the quality of the carving turn and the performance in para-alpine skiing. In general, it is thought that sit-skiers have more difficulty controlling their center of mass and making skis deflected than standing skiers (Langelier et al., 2013). However, no studies have investigated ski deflection during a run for sit-skiers. Recently, we developed a new method to measure ski deflection using a Fiber Bragg Grating sensor (hereinafter FBG) as an alternative method to the strain gauge that had been the mainstream method proposed by Yoneyama et al. (2008). Thus, this study aimed to reveal the ski deflection for a sit-skier using the FBG while comparing a standing skier.